54.2.4 problem 4

Internal problem ID [8536]
Book : Elementary differential equations. Rainville, Bedient, Bedient. Prentice Hall. NJ. 8th edition. 1997.
Section : CHAPTER 16. Nonlinear equations. Miscellaneous Exercises. Page 340
Problem number : 4
Date solved : Monday, January 27, 2025 at 04:11:15 PM
CAS classification : [[_1st_order, _with_linear_symmetries], _rational]

\begin{align*} 4 y^{3} {y^{\prime }}^{2}-4 x y^{\prime }+y&=0 \end{align*}

Solution by Maple

Time used: 0.147 (sec). Leaf size: 85

dsolve(4*y(x)^3*diff(y(x),x)^2-4*x*diff(y(x),x)+y(x)=0,y(x), singsol=all)
 
\begin{align*} y &= \sqrt {-x} \\ y &= -\sqrt {-x} \\ y &= \sqrt {x} \\ y &= -\sqrt {x} \\ y &= 0 \\ y &= \operatorname {RootOf}\left (-\ln \left (x \right )+2 \left (\int _{}^{\textit {\_Z}}-\frac {\textit {\_a}^{4}-\sqrt {-\textit {\_a}^{4}+1}-1}{\textit {\_a} \left (\textit {\_a}^{4}-1\right )}d \textit {\_a} \right )+c_{1} \right ) \sqrt {x} \\ \end{align*}

Solution by Mathematica

Time used: 0.360 (sec). Leaf size: 150

DSolve[4*y[x]^3*(D[y[x],x])^2-4*x*D[y[x],x]+y[x]==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to -\sqrt [4]{-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to -i \sqrt [4]{-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to i \sqrt [4]{-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to \sqrt [4]{-e^{c_1} \left (-2 x+e^{c_1}\right )} \\ y(x)\to 0 \\ y(x)\to -\sqrt {x} \\ y(x)\to -i \sqrt {x} \\ y(x)\to i \sqrt {x} \\ y(x)\to \sqrt {x} \\ \end{align*}